1995
DOI: 10.1116/1.579733
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal induced ring-cluster structures on Si(111)

Abstract: We characterize a ‘‘ring-cluster’’ (RC) structure produced by high temperature annealing of transition metals on Si(111), studied by scanning tunneling microscope and low-energy electron microscopy. This structure consists of a single metal atom on a substitutional site in the top layer of Si(111) plus an overlying ring of six Si adatoms with an unusual bridge bonded topology. We find that the same structure occurs for all near noble metals specifically Fe, Co, Ni, Pd, Pt and Ir. It does not occur for refracto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…1(b)). Our STM observations have revealed that the structure of the disordered regions is basically similar to that of the so-called ''1 · 1''-RC (ring-cluster) phase [16][17][18][19][20]. This phase is known to be induced by many silicide-forming metals (e.g., Co, Ni, Pd, Pt, Ir) and it comprises a disordered array of the ring clusters.…”
Section: Disordered Region Formationmentioning
confidence: 85%
“…1(b)). Our STM observations have revealed that the structure of the disordered regions is basically similar to that of the so-called ''1 · 1''-RC (ring-cluster) phase [16][17][18][19][20]. This phase is known to be induced by many silicide-forming metals (e.g., Co, Ni, Pd, Pt, Ir) and it comprises a disordered array of the ring clusters.…”
Section: Disordered Region Formationmentioning
confidence: 85%
“…19 -R23.4°, and (1 × 1)-RC phases on a Si(111) surface, [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and ´n 2 and 2 2-R45°p hases on a Si(100) surface 11,[21][22][23] have no analogous bulk silicide. Although the lattice mismatch between Si and bulk NiSi 2 is negligible (−0.44%), no epitaxial 2-D silicides corresponding to the low-index face of NiSi 2 or other bulk silicides are formed on Si substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Si on Ni, Ni-induced reconstructions on Si substrates do not have a uniform 2-D silicide covering the entire surface with a single phase. [10][11][12][13][14]16,17) This fact is due to the large diffusion of Ni into the bulk Si which prevents a flat 2-D silicide forming on Si substrates, 54) and before a uniform 2-D silicide is completed, deposited Ni atoms diffuse into the bulk Si and precipitate more stable 3-D silicides, which induce inhomogeneity of the surface layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STM micrographs at low (Figure a) and high (Figure d) magnification show that the terrace‐step bunch structure of the vicinal Si(111) substrate is covered by a thin quasi‐continuous flat and reconstructed film. Inside the holes in the film, a secondary phase of ring cluster (RC) patches—a well‐known sub‐monolayer (ML) surface structure of transition metal silicides—is clearly seen . The characteristic Si(111)‐(7 × 7) reconstruction could not be observed.…”
Section: Resultsmentioning
confidence: 99%